Positive Journalism in the Style of Republika Portal on the Issue of COVID-19 - Astrid, Andi Fauziah (Jurnal Mercusuar, 2020)
Information related to Covid-19 has become an infodemic that makes some people reject its truth. This happens because the circulating information tends to be frightening and makes people restless. Republika Online portal is present to provide positive information with the hashtag #goodnews. While some media outlets release information on the number of deaths and the severity of Covid-19, Republika presents Covid-19 information that gives hope to the public to remain optimistic in fighting this pandemic. This is in line with the presence of Positive Journalism which aims to provide constructive and solution-oriented things.